2016
DOI: 10.2147/ijn.s115044
|View full text |Cite
|
Sign up to set email alerts
|

Dual-function synthetic peptide derived from BMP4 for highly efficient tumor targeting and antiangiogenesis

Abstract: Angiogenesis plays a critical role in the growth and metastasis of cancer, and growth factors released from cancer promote blood-vessel formation in the tumor microenvironment. The angiogenesis is accelerated via interactions of growth factors with the high-affinity receptors on cancer cells. In particular, heparan sulfate proteoglycans (HSPGs) on the surface of cancer cells have been shown to be important in many aspects of determining a tumor’s phenotype and development. Specifically, the regulation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…38 Peptide (along with derivatives) based therapy supported with nano-modifications can serve as a better therapeutic approach to target the TME's cellular and non-cellular components. 12,15,20,96,123 These classes of drugs are known for their selectivity, efficiency, amphoteric nature and these are modifiers of biological processes, acting as signalling molecules and passing easily through plasma membrane. 96 A most common and effective biomarker in cancer is the low pH of cancer cells.…”
Section: Therapeutic Approaches To Modulate Tmementioning
confidence: 99%
See 1 more Smart Citation
“…38 Peptide (along with derivatives) based therapy supported with nano-modifications can serve as a better therapeutic approach to target the TME's cellular and non-cellular components. 12,15,20,96,123 These classes of drugs are known for their selectivity, efficiency, amphoteric nature and these are modifiers of biological processes, acting as signalling molecules and passing easily through plasma membrane. 96 A most common and effective biomarker in cancer is the low pH of cancer cells.…”
Section: Therapeutic Approaches To Modulate Tmementioning
confidence: 99%
“…123 Evidence has shown that a newly developed peptide with heparin-binding activity suppresses tumor progression and metastasis by blocking angiogenesis, acting as an angiogenesis inhibitor in targeting the TME. 20 Among other secreted proteins, evidences have supported the importance of extracellular secreted exosomal heat shock protein 60 (HSP60) as a modulator of TME. These HSP60 have been linked to the anticancer effects of Suberoylanilide hydroxamic acid, an inhibitor of histone deacetylase family of enzyme.…”
Section: Therapeutic Approaches To Modulate Tmementioning
confidence: 99%